Pediatric asthma and COVID-19 vaccination: unveiling patterns of hesitancy and acceptance - Marzieh Tavakol; Saber Gharagozlou; Mohammad Abbasi; Zahra Zamani; Mohammad Gharagozlou (SAGE Publishing, 2024)
Background: The global COVID-19 pandemic, declared in January 2020, necessitated urgent preventive measures, with vaccination as a key strategy. Despite progress in vaccine development and distribution, widespread hesitancy persists, impeding global disease control efforts. This study specifically explores COVID-19 vaccine hesitancy and acceptance among Iranian children with asthma, aiming to understand factors unique to this subgroup. Method: A cross-sectional investigation was carried out in an allergy clinic in Iran, including a total of 522 asthmatic children between the ages of 5 and 18 years. A comprehensive questionnaire, built upon previous studies, investigated the factors that influence vaccine hesitation and acceptance. Data pertaining to demographics, vaccination status, and factors influencing hesitancy or acceptance were collected. Results: Among the participants, 27.5% were administered the COVID-19 vaccine. Decisions were greatly influenced by family dynamics, with a notable association between parent and child vaccination. Children's vaccination rates were associated with their age and the frequency of COVID-19 diagnosis among their parents. The primary factors motivating individuals to get vaccinated were safety concerns (67.1%) and a strong belief in the severity of COVID-19 (43.4%). On the other hand, vaccine hesitancy resulted from concerns about potential adverse effects (77%), lack of confidence (28.3%), and a belief that children who had already contracted COVID-19 did not require vaccination (22.5%). Conclusion: The study highlights COVID-19 vaccine hesitancy and acceptance among asthmatic children in Iran, emphasizing parental decision-making factors. Tailored interventions are required due to the lower vaccination rate in this specific group. Healthcare providers play a vital role in influencing opinions, urging actions against misinformation, enhancing vaccine understanding, and promoting positive attitudes.